2020
DOI: 10.1002/jlb.1mr0520-014rr
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal regulation of dendritic cells: An intricate balance between migration and presentation for tumor therapy

Abstract: Dendritic cells (DCs) are the main players in many approaches for cancer therapy. The idea with DC tumor therapy is to promote activation of tumor infiltrating cytotoxic T cells that kill tumor cells. This requires that DCs take up tumor Ag and present peptides on MHC class I molecules in a process called cross-presentation. For this process to be efficient, DCs have to migrate to the tumor draining lymph node and there activate the machinery for cross-presentation. In this review, we will discuss recent progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 196 publications
(376 reference statements)
0
4
0
Order By: Relevance
“…These included classic DC maturation markers such as Cd80, Cd86, and Cd40 itself 83 , indicative of partial overlap with the canonical "mature DC" phenotype 84 . However, LIPSTIC-labeled DCs also upregulated multiple genes and signatures associated with cell migration, adhesion, and T cell chemotaxis 85 . Thus, the ability of DCs to access specific microanatomical compartments and to recruit T cells to these areas, previously shown to be functionally important for T cell responses [44][45][46]86 , is in fact one of the defining characteristics of the DCs capable of engaging T cells in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…These included classic DC maturation markers such as Cd80, Cd86, and Cd40 itself 83 , indicative of partial overlap with the canonical "mature DC" phenotype 84 . However, LIPSTIC-labeled DCs also upregulated multiple genes and signatures associated with cell migration, adhesion, and T cell chemotaxis 85 . Thus, the ability of DCs to access specific microanatomical compartments and to recruit T cells to these areas, previously shown to be functionally important for T cell responses [44][45][46]86 , is in fact one of the defining characteristics of the DCs capable of engaging T cells in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported a progressive decrease in cDCs1 in lung tumor draining LNs 36 . Both lysosomal stress 66,67 and increased GBP2 68 that we have discovered can change cytoskeleton dynamics and calcium signaling in cDCs1, decreasing their migration 69 . Accordingly, among the top down-regulated genes in our tumor cDC1 dataset there were several related to cytoskeleton and cell adhesion.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study reported a progressive decrease in cDC1s in tumor draining LNs and indicated a decrease in cDC1 migration rates through unknown mechanisms [26]. We have uncovered three factors that can all change the cytoskeleton dynamics and calcium signaling of cDC1s and thus may impede their migration to LNs[46]: lysosomal stress [47, 48], early apoptosis [49] and increased GBPs [50]. Interestingly, among the top down-regulated genes in tumor cDC1s there were several related to cytoskeleton and cell adhesion, further substantiating such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…DC uptake, antigen processing and presentation can be modulated in order to improve DC-mediated tumour therapy. Different actin regulators coordinate specific cell responses and it is possible that inhibition of specific actin regulators may be beneficial in supporting different stages of DC maturation and their functionality [25]. CK666 is an Arp2/3 inhibitor that stabilises the inactive state of the complex, blocking the movement of the Arp2 and Arp3 subunits into the activated filament-like (short pitch) conformation [26].…”
Section: Introductionmentioning
confidence: 99%